Persepsi Kepuasan Wisatawan terhadap Paket Wisata di Desa Karanggeneng, Purwobinangun, Pakem, Sleman - Suharto Suharto; Vandrias Dewantoro; Chandra Darmawati P. (Jurnal Dinamika Sosial Ekonomi, 2009)
This study aims to determine the perception of satisfaction of visitors tourists on package offered the Karanggeneng Tourism Village. The research method used in the method of survey sampling method was used accidental sampling of 80 samples from students, college students, employees and the general public Anal yats techniques using the Likert scalescore of 1-3. The results showed that visitors have a higher perception of satisfaction to the package tourism products, services and to facilities infrastructure able to provide a memorable service, outbound packets become the most preferred package visitors.Key words: perception, satisfaction, service, tourism,  outbound